Implementation of the Deep Learning Approach to Improve Students’ Science Literacy in IPAS Classes in the Fourth Grade of Madrasah Ibtidaiyah - Widiyanti Widiyanti; Sri Yulia Sari; Nisa Aulia (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to describe the implementation of the deep learning approach in improving students’ scientific literacy in IPAS learning in fourth-grade Madrasah Ibtidaiyah. This study employs a qualitative approach with a descriptive research design. The research subjects were teachers and fourth-grade students at Madrasah Ibtidaiyah. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of the deep learning approach in IPAS instruction can help students develop a deeper understanding of scientific concepts. This approach was applied through the principles of mindful learning, meaningful learning, and joyful learning, thereby making students more active, critical, and capable of relating the learning material to their daily lives. In addition, a more enjoyable learning atmosphere also increases students’ motivation to understand scientific phenomena in their surroundings. Thus, the application of the deep learning approach in IPAS instruction can serve as an effective alternative learning strategy to improve students’ science literacy in Madrasah Ibtidaiyah.